Power system protection in smart grid environments - Bansal, Ramesh (CRC Press, Taylor & Francis Group, 2019)
This book illustrates fault analysis, fuses, circuit breakers, instrument transformers, relay technology, transmission lines protection setting using DIGsILENT Power Factory. Intended audience is senior undergraduate and graduate students, and researchers in power systems, transmission and distribution, protection system broadly under electrical engineering.